E-marketing : theory and application - Dann, Stephen, 1973-; Dann, Susan J. (Houndmills, UK. : Palgrave MacMillan, 2011)
'A mix of academic rigor and practical application combining a strong theoretical framework from the academic peer reviewed literature with contemporary developments in internet technology, and their application to the e-marketing environment. Topics include consumer behavior, value creation, marketing strategy, implementation issues for e-marketing, and much more'--
Includes bibliographical references and index.
Keywords: Telemarketing; Internet; Consumer behavior